Implications and Practical Applications of the Chemical Speciation of Iodine in the Biological Context - Astrid N. Espino-Vázquez; Flor C. Rojas-Castro; Liria Mitzuko Fajardo-Yamamoto (MDPI AG, 2022)
Iodine is a highly reactive element with a single natural and stable isotopic form (127I). In the biosphere, it is one of the 30 essential elements for life, and its chemical speciation defines its availability and biological activities. The most relevant chemical species are iodate (IO3−) and iodide (I−) as the major sources of iodine, with molecular iodine (I2) and hypoiodous acid (HIO) as the most reactive species, and thyroid hormones (THs) as the representative organic compounds. In human biology, THs are master regulators of metabolism, while inorganic species serve for the iodination of organic molecules and contribute to the innate immune system and the antioxidant cellular defense. Additionally, I−, I2, δ-lactone (6-IL), and α-iodohexadecanal (α-IHDA) have shown therapeutic potential in counteracting oxidative stress, cancer, and inflammation. Both inorganic and organic species have applications in the health science industry, from the manufacturing of disinfection and wound care products to supplements, medicines, and contrast media for radiography. Even after nuclear disasters, intake of high doses of iodine prevents the accumulation of radioactive iodine in the body. Conversely, the controlled production of iodine radioisotopes such as 123I, 124I, 125I, and 131I is exploited in nuclear medicine for radiotherapy and diagnostics.